Impact of Baseline Muscle Mass and Myosteatosis on the Development of Early Toxicity During First-Line Chemotherapy in Patients With Initially Metastatic Pancreatic Cancer - Hong, Sun; Kim, Kyung Won; Park, Hyo Jung; Ko, Yousun; Yoo, Changhoon; Park, Seo Young; Khang, Seungwoo; Jeong, Heeryeol; Lee, Jeongjin (Frontiers in Oncology, 2022)
Objectives Although chemotherapy is the only treatment option for metastatic pancreatic cancer (PDAC), patients frequently encounter adverse events during chemotherapy leading deterioration of patients’ quality of life and treatment interruption. We evaluated the role of baseline CT-assessed body composition in predicting early toxicity during first cycle of the first-line chemotherapy in patients with metastatic PDAC. Methods This retrospective study included 636 patients with initially metastatic PDAC who underwent first-line chemotherapy from January 2009 to December 2019. Chemotherapy regimen, baseline laboratory data, and body composition parameters acquired from baseline CT were obtained. The skeletal muscle index (SMI) was used to identify patients with a low muscle mass (SMI < 41 cm2/m2 for women, and < 43 cm2/m2 [body mass index < 25 cm/kg2] or < 53 cm2/m2 [body mass index ≥ 25 cm/kg2] for men), and myosteatosis was defined as low-attenuated muscle area divided by skeletal muscle area (LAMA/SMA index) ≥ 20%. Univariate and multivariable binary logistic regression analyses were performed using bootstrapping with 500 interactions to identify predictors of grade 3–4 toxicity and any treatment-modifying toxicity which led to a dose reduction, delayed administration, drug skip or discontinuation. Results During the first cycle of the first-line chemotherapy, grade 3–4 toxicity and treatment-modifying toxicity occurred in 160 patients (25.2%) and in 247 patients (38.8%), respectively. The presence of both low muscle mass and myosteatosis was significantly associated with the occurrence of both grade 3-4 toxicity (odd ratio [OR], 1.73; 95% confidence interval [CI], 1.14–2.63) and treatment-modifying toxicity (OR, 1.83; 95% CI, 1.26–2.66) whereas low muscle mass alone did not. Conclusions The presence of both low muscle mass and myosteatosis assessed on baseline CT may be used to predict early chemotherapy-related toxicity in patients with metastatic PDAC.